Castleman Disease of the Parotid Gland: A Report of a Case - Fawaz Abo-Alhassan; Fatemah Faras; Jassem Bastaki; Mutlaq K. Al-Sihan (Case Reports in Otolaryngology)
Castleman disease is an extremely rare benign lymphoproliferative disorder of unknown etiology. It affects the lymphatic chain in anybody region, although the commonest site is the mediastinum. The head and neck region is the second most common site; however, the salivary glands are rarely affected. We report a case of a 29-year-old Asian lady who presented with a 2-year history of an enlarging left parotid mass. Histopathology of the excisional biopsy confirmed the diagnosis of Castleman disease.